Eulerian Multiphase Simulation of the Particle Dynamics in a Fluidized Bed Opposed Gas Jet Mill - Dyrney, Araujo dos Santos; Baluni, Shivam; Bück, Andreas (Processes, 2020)
The compressible and turbulent gas-solid multiphase flow inside a fluidized bed opposed jet mill was systematically investigated through numerical simulations using the Euler-Euler approach along with the kinetic theory of granular flow and frictional models. The solid holdup and nozzle inlet air velocity effects on the gas-solid dynamics were assessed through a detailed analysis of the time-averaged volume fraction, the time-averaged velocity, the time-averaged streamlines, and the time-averaged vector field distributions of both phases. The simulated results were compared with the experimental observations available in the literature. The numerical simulations contributed to a better understanding of the particle-flow dynamics in a fluidized bed opposed gas jet mill which are of fundamental importance for the milling process performance.
CRIS-Team WoS Importer:2021-01-15
Keywords: granular temperature; OpenFOAM; particle velocity; compressible flow; turbulent flow; comminution